Ensuring Citizens’ Well-Being in the EU: A Comparative Analysis of Fiscal Policies - Ulian, Galina; Covalschi, Tatiana (Acta Universitatis Danubius. Œconomica, 2025)
Objectives: This paper undertakes an analytical examination of the experiences of European Union member states with the objective of identifying exemplary practices that may be suitably adapted and implemented within the context of the Republic of Moldova. Prior Work: This paper is a part of the authors’ broader research on the role of fiscal policy in ensuring the citizens` well-being, conducted within the subprogram „Strengthening socio-economic and legal mechanisms to ensure the well-being and security of the citizens” (CONSEJ 01.05.02). Approach: In this paper the authors perform a comparative study of the main public finance indicators, such as the structure of public revenues and expenditures, the public budget balance, public debt. Results: Although there are fiscal rules applied in the EU member states, the fiscal policy in EU member states varies among countries. It is also noted that recent economic developments have had a negative impact on the sustainability of public finances in EU member states, with a negative impact on ensuring the well-being of citizens. Implications: The experiences of EU member states substantiate the imperative of maintaining fiscal discipline in the Republic of Moldova, particularly in light of its status as a candidate for EU accession. Value: This study constitutes an original analysis of the experiences of EU member states in promoting citizens’ well-being through fiscal policy, offering valuable insights and lessons for national public authorities in the Republic of Moldova.